Computer aided learning (cal) centers under sarva shiksha abhiyan: establishment and functioning - K, VIJAYARANI; S, SENTHILNATHAN (Journal of Management and Science, 2012)
Education is the process of modification of behaviors. In order to enhance the effectiveness of this process, several techniques, methods and approaches have been evolved, tried out and tested from time immemorial. Both Central and State Governments and NGOs have tried many innovations at all levels of education through several schemes. One such scheme is the Sarva Shiksha Abhiyan (SSA) which is Government of India‘s flagship programme for achievement of Universalization of Elementary Education (UEE) in a time bound manner, as mandated by 86th amendment to the constitution of India making free and compulsory education to the children of 6 – 14 years age group as a fundamental right.